O.J. : made in America [videorecording (DVD)] - Simpson, O. J., 1947-; Edelman, Ezra (30 for 30., 2016)
An essential examination of the rise and fall of Orenthal James Simpson, and parallels between his incredible story with that of race in America. This critically-acclaimed documentary series reveals how he first became a football star, why America fell in love with him off the field, what happened in the trial for his ex-wife's murder, and finally, why he is now sitting in jail for another crime 20 years later.